Drug Induced Steven- Johnson Syndrome (SJS) - Miya, Riyaz; Malpani, Ashok Kumar; Keri, Sangamesh; Panagaon, Rohit (Indian Journal of Pharmacy Practice)
Steven Johnson Syndrome (SJS) or Toxic Epidermal Necrolysis (TEN) is a life threatening immune complex mediated hypersensitivity reaction which mainly involves skin and mucous membrane. SJS is generally induced by the drugs. The manifestations include blisters on skin, facial swelling and hyper pigmentation. Here is a 28-yearold Indian male received Ofloxacin, Paracetamol and Phenobarbitone and experienced a severe skin reaction which was diagnosed as Stevens Johnson syndrome (SJS). The above drugs will be implicated in cases of Stevens Johnson Syndrome (SJS) / Toxic Epidermal Necrosis (TEN). There are few case reports of that have been associated with Stevens Johnson Syndrome (SJS)/ Toxic Epidermal Necrosis (TEN). We hope that this case report creates awareness to the health care professionals.
Keywords: SJS; TEN; Ofloxacin; Paracetamol; Phenobarbitone.